Why do Corsican Blue Tits Cyanistes caeruleus ogliastrae not use nest boxes for roosting? - Dhondt, André a.; Blondel, Jacques; Perret, Philippe (Journal of Ornithology, 2009)
We compared winter roosting behaviour of Blue Tits Cyanistes caeruleus in the mainland of southern France and on the island of Corsica in small-holed nest boxes. While in southern France Blue Tits use nest boxes for roosting, Corsican Blue Tits do not. We suggest that this behaviour is innate because Corsican wild-caught as well as F1 and F2 birds born in captivity do not use nest boxes in aviaries even when kept adjacent to mainland tits that sleep in boxes. We suggest that the cost/beneﬁt balance differs between mainland France and Corsica: in Corsica, the costs of roosting in the canopy are less than in mainland France because (1) predators, e.g. owls, are rare in Corsica while abundant on the mainland, (2) the permanent evergreen foliage of the dominant tree in Corsica, the holm oak, could be preferred to nest boxes which are not risk-free, and (3) the costs of using cavities for roosting could be higher in Corsica because of increased mammal predator pressure and higher ectoparasite load than on the mainland.
Keywords: á parasitism á; Cyanistes caeruleus ogliastrae; cyanistes caeruleus ogliastrae á; Life-history trait; life-history trait á predation; Parasitism; Predation; Small-holed nest box